THE NON/POSSIBLE CONSTRUCTION IN THE NOVEL "GENESIS" (“BITIETO”) BY VLADIMIR ZAREV - Velika Gyulemerova (Езиков свят)
The present text is part of a larger study on the problem of the biblical parable of the prodigal son and its implicit reflection in Bulgarian literature. Vladimir Zarev’s novel “Genesis” poses the problem of crime and its inheritance by sons in the family. The novel is marked by the sign of transgression in its various possible realizations – murder, suicide, violation of sexual prohibitions. The text problematizes the image of the father, as a figure setting the value paradigm in the lives of the sons. This article proposes that the father is the bearer of the rebellion in the family – he is the prodigal son, who has crossed the line of no longer fearing God and of disrespecting the commandments which have guaranteed harmony and integrity of being with others. The predatory is implicit in the nature of the genus – it is a subconscious impulse for transgression. The novel’s plot focuses on the first-born son and the resulting tension. The sons yearn to build a place where they can find peace and to break away from ancestral sin. The text poses the problem of existential loneliness and inner dissatisfaction of the characters, but also of their inability to find a divine providence for their own existence.